FUNCTIONS OF THE RUSSIAN RURAL AREAS AND THEIR FULFILLMENT - Gennadievich Paptsov, Andrei; Vasilievna Bondarenko, Lyudmila (Revista Inclusiones, 2020)
In the article the natural, material, and human potential of the Russian rural areas has been defined. Their national and internal functions aimed at life support, preservation, and development of the population have been analyzed. The imbalance between the fulfillment by the rural areas of their main national production function (ensuring food security and independence of the country) and the standard of the population’s life has been noted. The comparative analysis has been made in relation to the goals of the State Program for the Integrated Development of the Rural Areas and Its Resource Support. The measures to legally prioritize the development of the rural areas have been suggested.